AN OVERVIEW OF UNIVERSITY, TRAINING, AND CAREER QUALIFICATIONS: A FOCUS ON THE SIGNIFICANCE AND CONTRIBUTIONS TO THE JOB MARKET AND ENTREPRENEURSHIP IN ALGERIA - Fateh Djebli,; Wahid Draouet,; Said Mansour, (International Journal of Innovative Technologies in Social Science, 2025)
The professional future and employment prospects are the main worries for young academics, including those based in Algeria. While young people are engaged in their university education, they are also actively seeking ways to enhance their skills and talents. One of the most critical contemporary issues and problems faced by young academics is the need to acquire professional qualifications and prepare for entry into the job market and entrepreneurship. Algerian universities are dedicated to customizing their training programs in order to cater to the demands of the job market. Due to the state's focus on entrepreneurship and the successful endeavors of many young individuals in self-employment, they actively promote creativity and personal growth, particularly in light of the opportunities presented by the digital era. Our article examines how Algerian university training programs contribute to preparing young Algerian students for the job market and entrepreneurship.